(untitled) (International Journal of Engineering and Computer Science, 2018)
The high growth within the networking technology leads a typical culture for interchanging of the digital pictures terribly drastic. Thus, it’s additional vulnerable of duplicating of digital image and re-distributed by hackers. So the knowledge needs to be protected whereas sending it, Sensitive data like credit cards, banking transactions and social insurance numbers have to be compelled to be protected. For this several cryptography and decoding techniques are a unit existing that area unit accustomed avoid the knowledge stealing. In the recent days of the web, the cryptography and decoding of information play a serious role in securing the information in on-line transmission focuses chiefly on its security across the web. Totally different cryptography and decoding techniques are units accustomed defend the confidential knowledge from unauthorized use. In this paper, a review of the cryptography based techniques has proposed. This review contains the working, merits, demerits of the current encryption decryption techniques.